Managers are potential levers of discrimination within organizations: the role of group identification, assimilation endorsement and power. Issue 8 (22nd March 2015) - Courtois, Marie; Herman, Ginette
Abstract Two studies examined the relationship between identification with a high‐position group in organizational settings (managers) and bias toward immigrants. In Study 1, (N = 182; N = 145), results showed positive relationships between identification with the managers' group and both in‐group bias and prejudiced attitudes, indirectly through assimilation endorsement. In Study 2 (N = 117), in addition to replicating the results of Study 1, we found a significant interaction, revealing that power moderated the link between identification with a high‐position group and bias. Moderated mediation analysis indicated that linking managers' group identification to bias and prejudiced attitudes through assimilation was only significant for high perceived power. Results are discussed in light of interethnic ideologies and the social identity theory. Some practical implications are provided.